Hubungan Edukasi Kesehatan dengan Pencegahan Perilaku Merokok Siswa (Journal of Telenursing (JOTING), 2024)
This study aimed to determine whether there is a relationship between health education and the prevention of smoking behavior among students at SMA Negeri 11 Makassar. This research method is quantitative and uses a cross-sectional method. The results of this study indicate that the analysis using the chi-square test had a significance level. The statistical test results using chi-square obtained the test results p = 0.001. because the p-value